A Correlation Study of the Colorectal Cancer Statistics and Economic Indicators in Selected Balkan Countries - Berislav Vekic; Berislav Vekic; Viktorija Dragojevic-Simic; Viktorija Dragojevic-Simic; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Mihajlo Jakovljevic; Marko Kalezic; Zagor Zagorac; Sasa Dragovic; Rastko Zivic; Rastko Zivic; et al. (Frontiers Media S.A., 2020)
Colorectal cancer (CRC) is one of the most commonly diagnosed malignant neoplasms. The aim of the study was to evaluate and correlate most important epidemiological and economic indicators of CRC in 11 selected Balkan countries. The number of new CRC cases was 56,960, and the highest 5-year CRC prevalence was in Slovenia, Croatia, and Greece. Age-standardized CRC incidence rates were highest in Slovenia, Serbia, and Croatia, and age-standardized mortality rates were highest in Croatia, Serbia, and Bulgaria. Current Health Expenditure as % of Gross Domestic Product was the highest in Bosnia and Herzegovina and Serbia. The GDP per capita levels have shown positive correlation with the CRC incidence rate and prevalence. Absolute numbers of new and death-related CRC cases and 5-year prevalence in absolute numbers have shown strong positive correlation with GDP in million current US$. It has been shown that various economic indicators can be linked to the rate of incidence and prevalence of the CRC patients in the selected Balkan countries. Therefore, economic factors can influence the epidemiology of CRC, and heavy CRC burden in the Balkan region may be one of the indexes of the economic development.